Solid state physics - Hunklinger, Siegfried; Enss, Christian (Berlin : De Gruyter, 2022)
This highly regarded textbook provides a general introduction to solid state physics. It covers a wide range of physical phenomena occurring in solids and discusses fundamental concepts for describing them. Traditional themes are complimented by modern topics, like low dimensional systems, strongly correlated materials, nanoscale systems and non-crystalline solids, which are gaining increasing technical and scientific importance. Helpful for exam preparation are numerous exercises in all chapters.
Includes index
Keywords: Electrons in solids; Magnetism; Semiconductor; Condensed Matter Physics